Translating culture - Kočan, Kristina (ELOPE (Ljubljana), 2015)
The paper interrogates cultural specifics of contemporary African American poetry and exhibits translation problems when translating this poetic work. African American writers have always included much of their cultural heritage in their writing and this is immediately noticed by a translator. The cultural elements, such as African American cuisine, attire and style in general, as well as spiritual and religious practices, often play a significant role for African American poets who are proclaiming their identity. Moreover, the paper presents the translation problems that emerge when attempting to transfer such a specific, even exotic, source culture into a target culture, like Slovene. The goal is to show to what extent contemporary African American poetry can successfully be translated into the Slovene language and to highlight the parts that inevitably remain lost in the translation process.
Keywords: afriško ameriška kultura; afriško ameriška poezija; ciljna kultura; izvirna kultura; prevajanje; translation